Allergen immunotherapy for insect venom allergy: a systematic review and meta‐analysis. Issue 3 (25th January 2017) - Dhami, S.; Zaman, H.; Varga, E.‐M.; Sturm, G. J.; Muraro, A.; Akdis, C. A.; Antolín‐Amérigo, D.; Bilò, M. B.; Bokanovic, D.; Calderon, M. A.; Cichocka‐Jarosz, E.; Oude Elberink, J. N. G.; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing the EAACI Guidelines on Allergen Immunotherapy (AIT) for the management of insect venom allergy. To inform this process, we sought to assess the effectiveness, cost‐effectiveness and safety of AIT in the management of insect venom allergy. Methods: We undertook a systematic review, which involved searching 15 international biomedical databases for published and unpublished evidence. Studies were independently screened and critically appraised using established instruments. Data were descriptively summarized and, where possible, meta‐analysed. Results: Our searches identified a total of 16 950 potentially eligible studies; of which, 17 satisfied our inclusion criteria. The available evidence was limited both in volume and in quality, but suggested that venom immunotherapy (VIT) could substantially reduce the risk of subsequent severe systemic sting reactions (OR = 0.08, 95% CI 0.03–0.26); meta‐analysis showed that it also improved disease‐specific quality of life (risk difference = 1.41, 95% CI 1.04–1.79). Adverse effects were experienced in both the build‐up and maintenance phases, but most were mild with no fatalities being reported. The very limited evidence found on modelling cost‐effectiveness suggested that VIT was likely to be cost‐effective in those at high risk of repeated systemic sting reactions and/or impaired quality of life. Conclusions: The limited available evidence suggested that VIT is effective in reducing severe subsequent systemic sting reactions and in improving disease‐specific quality of life. VIT proved to be safe and no fatalities were recorded in the studies included in this review. The cost‐effectiveness of VIT needs to be established.